Economic and non-economic returns to Communist Party membership in Viet Nam - Thomas Markussen; Ngo Quang-Thanh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Single-party political systems exist in a number of countries, such as China and Viet Nam. In these countries, party membership is potentially an important source of economic and social status. This paper investigates these effects and the mechanisms behind them. In particular, we use household- and individual-level panel data to analyse the causes and consequences of Communist Party membership in rural areas of Viet Nam. Fixed effects models are employed to control for unobserved differences between party members and others. Results suggest that party membership has a moderate positive effect on income, on the order of seven per cent, and a large positive effect on subjective well-being, even after controlling for income. Party membership is closely associated with working for the government but also appears to increase the propensity to use credit and to boost income from farm and non-farm enterprises. There are strong gender effects: men are several times more likely to be party members than women, and the effects of membership on income and subjective well-being are only present among men. Overall, results confirm that in spite of pro-market economic reforms, Communist Party membership continues to be of high value in rural Viet Nam.
Keywords: D31; D73; H7; I31; P26; 330; Communist Party membership; income; credit; subjective well-being; Viet Nam